1992
DOI: 10.1254/jjp.60.369
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Inhibits the Progression Phase of Subcultured Endothelial Cell Proliferation in Rat Aorta

Abstract: ABSTRACT-The anti-proliferative effects of heparin on subcultured endothelial cells (EC) of rat aorta were investigated to determine whether heparin inhibits the competence phase or the progression phase in the cell cycle using the starting time and the rate of proliferation. Fetal bovine serum (FBS) stimulated EC proliferation increased to 1.5-times in cell number, but decreased to 0.5-times in 3H-thy midine incorporation, compared with the proliferation of rat primary cultured smooth muscle cells (SMC). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Heparin and heparan sulfate are complex glycosaminoglycans that exert antiproliferative effects in different cell types [32,33,14–16]. Consonant with growth inhibition, heparin inhibits the expression of the early proto‐oncogenes c‐fos and c‐myc by acting selectively on a PKC‐dependent pathway [18–20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin and heparan sulfate are complex glycosaminoglycans that exert antiproliferative effects in different cell types [32,33,14–16]. Consonant with growth inhibition, heparin inhibits the expression of the early proto‐oncogenes c‐fos and c‐myc by acting selectively on a PKC‐dependent pathway [18–20].…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of PKC in transducing growth regulatory signals is also highlighted by the finding that the down‐regulation of PKC‐dependent pathways elicits growth inhibitory responses. In particular, glycosaminoglycan‐mediated inhibition of cell proliferation [14–16] and angiogenesis [17] has been associated, at least in part, to the ability of heparin and heparan sulfate to counteract PKC‐mediated events [18–20]. In this regard, we have recently shown that heparin markedly reduced both the serum‐ and phorbol ester‐stimulated DNA synthesis in HEC by eliciting the down‐regulation of the PKC‐mediated ornithine decarboxylase gene expression (ODC) [21].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously analyzed PDGF and FBS-stimulated competence of DNA synthesis by a convenient method (7,12). Heparin does not inhibit the PDGF-induced compe tence phase, suggesting that it inhibits the progression phase in the SMC (7).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of indices of competence and progression inhibi tions We analyzed the inhibitory effects of cnidium rhizome derived phthalides on competence and progression phases of SMC proliferation by using the convenient assay reported previously (7,12). Proliferation lines of the SMC number from 3 x 104 to 6 x 104 cells/well as a func tion of culturing time were fitted to the individual data of SMC number by the least-squares method.…”
Section: Assay Of Smc Proliferationmentioning
confidence: 99%
See 1 more Smart Citation